Persepsi Tayangan Sinetron Anak Jalanan Di Rcti Oleh Masyarakat Di Lingkungan Kelurahan Koto Baru, Pasaman Barat (International Forum of Researchers and Lecturers, 2023)
This study aims to find out about the perception of street children soap operas on RCTI by the Community in the Koto Baru Village, West Pasaman. The initial problems with television shows, especially the soap opera